PENGARUH SUBSTITUSI RANSUM KOMERSIAL DENGAN KANGKUNG AIR AFKIR TERFERMENTASI TERHADAP KINERJA EKONOMI AYAM KAMPUNG SUPER JANTAN (The effect of commercial ration substitution with fermented reject water kale on the economic performance of ......) - Imakulata A. Putri; Franky M S Telupere; Ulrikus R. Lole; Arnoldus Keban (Universitas Nusa Cendana, 2023)
This study aims was to analyse the effect of substitution commercial ration with fermented reject water kale on the economic performance of super rooster native chickens. The material used was 80 heads of 5 week old super rooster native chickens. This study used a complete randomized design (RAL) with 4 treatments of 5 replications with each replication consisted of 4 super rooster native chickens. The treatment tried was R0: 100% commercial ration, R1: 90% commercial ration + 10% fermented reject water kale, R2: 80% commercial ration + 20% fermented reject water kale, R2: 70% commercial ration + 30% fermented reject water kale. The variables observed were production costs, revenue, income, IOFC business feasibility analysis B/C, R/C and (production BEP and price BEP). The results of this research showed that substitution commercial ration with fermented reject water kale had a significant effect on of the economic performance of super rooster native chickens. The best treatment is R3 because production costs are low but get optimum income.